IMPORTANT FACTORS IN PREPARING STUDENTS FOR PROFESSIONAL ACTIVITIES BASED ON INTEGRATION OF NATURAL SCIENCES (Modern education and development, 2025)
The article analyzes the important factors of preparing students for professional activity on the basic of the integration of graphic sciences and the results of research work carried out by several scientists in this field. On the basic of these analyzes, the integration of graphic disciplines was developed and a questionnaire on professional activities was conducted among students, and their results are also covered in the article. The teaching of graphic sciences, which is a key factor in the development of students in the field of graphic design, design and their integration, is based on clear evidence and conclusions and recommendations that in the future these personnel will play a key role in mastering the field and their professional activities.